Antiprotozoal Activity Against Entamoeba histolytica of Flavonoids Isolated from Lippia graveolens Kunth - Quintanilla Licea, Ramiro; Vargas Villarreal, Javier; Verde Star, María Julia; Rivas Galindo, Verónica Mayela; Torres Hernández, Ángel David (Molecular Diversity Preservation International, 2020)
Amebiasis caused by Entamoeba histolytica is nowadays a serious public health problem worldwide, especially in developing countries. Annually, up to 100,000 deaths occur across the world. Due to the resistance that pathogenic protozoa exhibit against commercial antiprotozoal drugs, a growing emphasis has been placed on plants used in traditional medicine to discover new antiparasitics. Previously, we reported the in vitro antiamoebic activity of a methanolic extract of Lippia graveolens Kunth (Mexican oregano). In this study, we outline the isolation and structure elucidation of antiamoebic compounds occurring in this plant. The subsequent work-up of this methanol extract by bioguided isolation using several chromatographic techniques yielded the flavonoids pinocembrin (1), sakuranetin (2), cirsimaritin (3), and naringenin (4). Structural elucidation of the isolated compounds was achieved by spectroscopic/spectrometric analyses and comparing literature data. These compounds revealed significant antiprotozoal activity against E. histolytica trophozoites using in vitro tests, showing a 50% inhibitory concentration (IC50) ranging from 28 to 154 µg/mL. Amebicide activity of sakuranetin and cirsimaritin is reported for the first time in this study. These research data may help to corroborate the use of this plant in traditional Mexican medicine for the treatment of dyspepsia.